Evaluasi Permasalahan Dead Stock Sparepart Menggunakan Pendekatan RCA untuk Meningkatkan Efektivitas Manajemen Persediaan di PT. R - Susanti, Heni Dewi; Septiani, Riana; Pratiwi, Mirandhi; Sundari, Susanti (Fakultas Teknik Universitas Tulang Bawang, 2026)
Suboptimal warehouse management can lead to dead stock, which refers to spare parts inventory that is not used for a certain period and may accumulate, resulting in financial losses for the company. This issue can arise due to weak inventory control, inaccurate stock records, and purchasing plans that are not based on actual usage data. This study aims to identify the causes of dead stock using Root Cause Analysis (RCA) to determine the root causes and Failure Mode and Effect Analysis (FMEA) to analyze potential failures and determine risk priorities based on the Risk Priority Number (RPN). The results show that the main factors causing dead stock include inaccurate inventory data, purchasing planning not based on actual usage, the absence of standard operating procedures (SOP) for stock management, and the lack of an integrated inventory management system. Based on the RPN calculation, inaccurate inventory data is the highest priority with an RPN value of 392, followed by unused spare parts (336), and full warehouse capacity and unutilized spare parts (252). These findings are expected to support improvements in inventory management to minimize the occurrence of dead stock. Keywords: Dead Stock, FMEA, Inventory Management, RCA, RPN